Isolation of maslinic acid from the leaves of Bixa orellana - Simpol, L (Archīum Ateneo, 1989)
Maslinic acid was isolated and identified as an antimicrobial constituent from the leaves of Bixa orellana. Studies on the antimicrobial activity of the plant extract and maslinic acid indicate that this compound is not the only antimicrobial constituent in the plant and that its action may be enhanced synergistically by other compounds in the plant.